The Manusmrti : with the commentary Manvarthamuktāvali of Kullūka, various redings, foot-notes, indices etc - Manu (SAMP early 20th-century Indian books project, 1946)
Classical work on Hindu social and religious laws; includes Manvarthamuktāvalī commentary of Kullūkabhatta.